2023
DOI: 10.3390/en16031058
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Thermal Performance Analysis of PCM-Incorporated Glazing Units Combined with Passive and Active Techniques: A Review Study

Abstract: The building envelope provides thermal comfort, an excellent visual view, and sunlight for the occupants. It consists of two parts: (i) an opaque (non-transparent) part (e.g., walls and roofs) and (ii) a transparent part (e.g., windows, curtain walls, and skylight devices). Recently, the use of fully-glazed facades, especially in large cities, has increased due to their aesthetical and structural advantages. This has led this study to review the performance of the currently passive smart glazing technologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Depending on the WWR, climate, type, and configuration, PV window glazing systems have the capacity for energy savings of around 12% to 76% [64]. By combining PV glazing systems with other technologies, it becomes possible to enhance the thermal performance of smart glazing solutions, resulting in improved energy efficiency.…”
Section: Energy Performance Evaluation Of Glazing Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the WWR, climate, type, and configuration, PV window glazing systems have the capacity for energy savings of around 12% to 76% [64]. By combining PV glazing systems with other technologies, it becomes possible to enhance the thermal performance of smart glazing solutions, resulting in improved energy efficiency.…”
Section: Energy Performance Evaluation Of Glazing Systemsmentioning
confidence: 99%
“…Regarding curtain selection, it was discussed that overhangs outperformed interior blinds by saving energy by around 2% to 10% in hot climates [53]. Shading systems have the potential to yield energy savings ranging from 10% to 75% annually, depending on factors such as the type of glazing, climate conditions, and the positioning of the shading devices [64]. Ganji Kheybari et al [73] stated that the literature showed that automated dynamic shading could save more energy than manual operations or static systems.…”
Section: Energy Performance Evaluation Of Glazing Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…reviewed the different concepts related to PCMs and details of the different types of PCMs according to climate Xu et al (2022). prepared a phasechange gel with relatively high melting enthalpy, better leak proof characteristics, better thermal insulation, besides increasing time lag and lowering peak temperature Arasteh et al (2023). reviewed energy and thermal performance of PCMincorporated glazing units combined with passive and active techniques including current passive smart glazing technologies, whileMichael et al (2023) provided a review on established and emerging glazing technologies and the inclusion of multiple functionalities to improve overall building performance.…”
mentioning
confidence: 99%